Open label, single arm, interventional multi-centered study to evaluate the efficacy and biophysical response of topical Soteri Skin cream in following skin conditions: atopic dermatitis, eczema, psoriasis and rosacea - Bedi, Guneet; Dash, Pratisha P.; Pielak, Rafal M. (International Journal of Research in Dermatology, 2022)
Background: Eczema, also known as dermatitis, is characterized by skin inflammation, which presents as pruritus, skin dryness and erythema. Soteri cream, which was used in the study, contains Helianthus annus oil, glycerin, sodium hyaluronate, niacinamide and various ceramides. Niacinamide upregulates epidermal ceramide synthesis; thereby, strengthening epidermal barrier. Methods: The study was conducted on 30 patients in total, out of which, 5 patients were of scalp (3) and palmar psoriasis (2), 10 of eczema, 10 of atopic dermatitis and 5 of rosacea. The above patients were the ones coming to Aayna clinic for their respective skin concerns. After doing clinical examination and taking written consent, patients were given Soteri skin cream, to apply twice daily on the area of concern. Follow up was done fortnightly for a month. Patient’s assessment in follow up visits was done with clinical photographic, along with dermoscopic photographic assessment after a month and by filling proforma for effects and side effects using VAS and SCORAD score (for atopic dermatitis). Results: Complete symptomatic and visual improvement was seen in 3 patients of eczema, 2 of rosacea, 1 of scalp psoriasis and 6 of atopic dermatitis. Conclusions: Soteri skin cream with its unique formulation of ceramides and niacinamide resulted in significant improvement in psoriasis, hand and nummular eczema, atopic dermatitis and rosacea. It is a steroid free, valuable line of treatment for chronic eczema.